2022
DOI: 10.2967/jnumed.121.263039
|View full text |Cite
|
Sign up to set email alerts
|

Tracking Innate Immune Activation in a Mouse Model of Parkinson’s Disease Using TREM1 and TSPO PET Tracers

Abstract: Parkinson's disease (PD) is associated with aberrant innate immune responses, including microglial activation and infiltration of peripheral myeloid cells into the central nervous system (CNS). Methods to investigate innate immune activation in PD are limited and have not yet elucidated key interactions between neuroinflammation and peripheral inflammation. Translocator protein 18 kDa (TSPO)-positron emission tomography (PET) is a widely evaluated imaging approach for studying activated microglia and periphera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…In an ischemic stroke model, mTrem1 activated the NF-κB signaling pathway and NLRP3 inflammasome via its interaction with SYK in microglia [ 11 ]. Besides, the protein could be adopted as a reliable PET probe to visualize the presence of early immune activation in PD and MS [ 58 , 59 ]. Therefore, neuroinflammation as the thread connecting the above diseases may explain the null results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…In an ischemic stroke model, mTrem1 activated the NF-κB signaling pathway and NLRP3 inflammasome via its interaction with SYK in microglia [ 11 ]. Besides, the protein could be adopted as a reliable PET probe to visualize the presence of early immune activation in PD and MS [ 58 , 59 ]. Therefore, neuroinflammation as the thread connecting the above diseases may explain the null results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have utilized PET to directly detect changes occurring in the periphery. Lucot et al recently reported whole-body imaging of innate immunity in 6-OHDA rats using the third-generation TSPO tracer [ 18 F]GE-180 combined with [ 64 Cu]TREM1-mAb, which targets the inflammation amplifier triggering receptor expressed on myeloid cells 1 (TREM1) [147]. In addition, the cholinergic tracers [ 11 C]donepezil and [ 18 F]fluoroethoxy-benzovesamicol (FEOBV) have been used to assess the levels of acetylcholinesterase density in the gastrointestinal tract and gastrointestinal parasympathetic innervation in PD patients [148,149].…”
Section: Emerging Targets and Pet Tracersmentioning
confidence: 99%
“…In some cases, radiolabeled antibodies can enter the brain by attachment to (immune) cells that become privy to the CNS. 104 Alternatively, CNS targets can sometimes be imaged with antibodies via a disrupted or "leaky" BBB, as with some cancers 82,105 (Table 2), neuroinflammation, 104 and multiple sclerosis. 81 However, to expand the use of antibodies in diagnosis and treatment of CNS conditions, reliable engineered methods of delivering antibodies across an intact BBB are critical.…”
Section: Beta Therapymentioning
confidence: 99%
“…Despite this, there are some methods by which antibodies inadvertently gain access to the CNS, and a number of reports exist of PET imaging of CNS targets using antibody platforms. In some cases, radiolabeled antibodies can enter the brain by attachment to (immune) cells that become privy to the CNS 104 . Alternatively, CNS targets can sometimes be imaged with antibodies via a disrupted or “leaky” BBB, as with some cancers 82,105 (Table 2), neuroinflammation, 104 and multiple sclerosis 81 .…”
Section: Challenges Limitations and Remaining Questionsmentioning
confidence: 99%